Regulatory pathways and guidelines for nanotechnology-enabled health products: a comparative review of EU and US frameworks - Rodríguez-Gómez, Francisco D.; Monferrer, Dominique; Penon, Oriol; Rivera-Gil, Pilar (Frontiers in Medicine, 2025)
The integration of nanotechnology into healthcare has introduced Nanotechnology-Enabled Health Products (NHPs), promising revolutionary advancements in medical treatments and diagnostics. Despite their potential, the regulatory navigation for these products remains complex and often lagging, creating barriers to their clinical application. This review article focuses on dissecting the regulatory landscape for NHPs, particularly in the European Union and the United States, to identify applicable requirements and the main regulatory guidelines currently available for meeting regulatory expectations.